2004
DOI: 10.1677/erc.1.00792
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of AgNOR counts and nuclear DNA content to survival in patients with parathyroid carcinoma

Abstract: The aim of this study was to evaluate the usefulness of DNA flow cytometry to determine tumor nuclear DNA index (DI), and nucleolar organizer region protein counts visualized by the argyrophil (AgNOR) technique, in confirming diagnosis and predicting clinical outcome of patients with parathyroid carcinoma (PC). We reviewed paraffin-embedded tissue sections, from 15 patients (median age 63 years, range 30-68 years) with PC who died of the disease, which were randomly compared with tissue sections from 15 age-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Although parathyroid carcinoma (PC) is an uncommon finding, accounting for only 1-2% of patients with primary hyperparathyroidism (PHPT); a relatively higher incidence has been reported in Italy and Japan, in consistent with our study (28,29). Another possible etiology that can explain the higher incidence may be the fact that our hospital is a tertiary center receiving more complicated cases who are candidates for surgery.…”
Section: Discussionsupporting
confidence: 86%
“…Although parathyroid carcinoma (PC) is an uncommon finding, accounting for only 1-2% of patients with primary hyperparathyroidism (PHPT); a relatively higher incidence has been reported in Italy and Japan, in consistent with our study (28,29). Another possible etiology that can explain the higher incidence may be the fact that our hospital is a tertiary center receiving more complicated cases who are candidates for surgery.…”
Section: Discussionsupporting
confidence: 86%
“…The stain has been widely applied in a variety of cell kinetic studies, using the mean number of argyrophil "(Ag) NORs" of the tumour cells mainly as a marker for cell proliferation. The staining method, initially developed by Goodpasture & Bloom (42), modified by Howell & Hsu (45) and Li et al (46), has provided additional information to predict malignancy in some endocrine tumours (47)(48)(49).…”
Section: Silver Stainsmentioning
confidence: 99%
“…The results of the present study also showed that samples with high AgNOR were showing aneuploid DI and high SPF. Thus, DI and AgNOR are both useful in confirming the diagnosis [37] and high AgNOR count holds promise for the prediction of disease aggressiveness [33, 35, 38]. …”
Section: Discussionmentioning
confidence: 99%